THE FUNCTIONAL, RHEOLOGICAL AND SENSORY ATTRIBUTES OF TULSI (HOLY BASIL, OCIMUM SANCTUM) EXTRACT BASED HERBAL ICE-CREAM - SWASHANKH KUMAR; D. C. RAI; DINKER SINGH (The Bioscan, 2012)
Research was conducted to examine the effect of Tulsi as an herb on the functional, rheological and textural characteristics of ice-cream desserts in relation to their sensory attributes. The objective of the present research was to develop improved herbal based ice-cream with health benefits beyond those of traditionally formulated dairy products. The product was formulated with different levels of herbal extract at 2.0%, 3% and 4.0%. There was a proportionate decrease in the fat, protein, reducing sugars, non-reducing sugars and total solids (TS) in the experimental samples with increasing the levels of Tulsi extract compared to control. Addition of Tulsi extract to ice-cream was shown to decrease viscosity of the ice-cream mix and decrease melting rate of the resulting herbal ice-cream based on sensory evaluation, the order of preference was T2 (3%) > T1 (2.0%) > T0 (0%) > T3 (4.0%).